Evaluation and Management of Patellar Instability in Pediatric and Adolescent Athletes. (March 2015) - Khormaee, Sariah; Kramer, Dennis E.; Yen, Yi-Meng; Heyworth, Benton E.
Context: The rising popularity and intensity of youth sports has increased the incidence of patellar dislocation. These sports-related injuries may be associated with significant morbidity in the pediatric population. Treatment requires understanding and attention to the unique challenges in the skeletally immature patient. Evidence Acquisition: PubMed searches spanning 1970-2013. Study Design: Clinical review. Level of Evidence: Level 5. Results: Although nonoperative approaches are most often suitable for first-time patellar dislocations, surgical treatment is recommended for acute fixation of displaced osteochondral fractures sustained during primary instability and for patellar realignment in the setting of recurrent instability. While a variety of procedures can prevent recurrence, the risk of complications is not minimal. Conclusion: Patellar stabilization and realignment procedures in skeletally immature patients with recurrent patellar dislocation can effectively treat patellar instability without untoward effects on growth if careful surgical planning incorporates protection of growth parameters in the skeletally immature athlete.